2015
DOI: 10.1108/lm-04-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Library and Information Science in a rapidly changing information landscape

Abstract: Users who downloaded this article also downloaded: (2015),"Reducing library space can promote the shift from storage of print-collections towards a learning-centre without limiting the access to information", Library Management, Vol. 36 Iss 8/9 pp. 685-689 http://dx.(2015),"Public library managers' descriptions of political attention", Library Management, Vol. 36 Iss 8/9 pp. 673-684 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…Although prior knowledge and employment prospects feature heavily in decisions to enter the profession (Ard et al, 2006; Cherry et al, 2011), additional factors determine why people choose librarianship. The desire to build community and work with the public can also influence a librarian’s decision to enter the profession (Bello, 1996; Dali and Caidi, 2016; Ho et al, 2018; Moniarou-Papaconstantinou et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although prior knowledge and employment prospects feature heavily in decisions to enter the profession (Ard et al, 2006; Cherry et al, 2011), additional factors determine why people choose librarianship. The desire to build community and work with the public can also influence a librarian’s decision to enter the profession (Bello, 1996; Dali and Caidi, 2016; Ho et al, 2018; Moniarou-Papaconstantinou et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pragmatic reasons such as having flexible hours and the promise of work/life balance have been said to attract individuals to a career in schools (Walker & Calvert, 2016), but it is the gratifying nature of the work itself that sustains interest in this career. In studies of school library professionals it has been found that there are deep, personal connections to the work; notably, a lifelong passion for books and reading, a connection to the library environment, and a desire to work or help people (Jones, 2010;Moniarou-Papaconstantinou, Vassilakaki, & Tsatsaroni, 2015;Shannon, 2008).…”
Section: Ericksonmentioning
confidence: 99%
“…With respect to LIS, a significant amount of research literature focused on individuals’ choice of LIS (e.g. Lo et al, 2015, 2017; Moniarou-Papaconstantinou et al, 2015). Regarding the positions of LIS students as agents operating in the field of HE, a number of studies examine students’ perceptions about the LIS discipline (Cherry et al, 2011; Dali and Caidi, 2016; Hallam and Partridge, 2005; Mansourian, 2010; Tiamiyu, et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%